2016
DOI: 10.1002/cbdv.201500282
|View full text |Cite
|
Sign up to set email alerts
|

13,14‐seco‐Withanolides from Physalis minima with Potential Anti‐inflammatory Activity

Abstract: Four new 13,14-seco-withanolides, minisecolides A - D (1 - 4), together with three known analogues 5 - 7, were isolated from the whole plants of Physalis minima. The structures of new compounds were determined on the basis of spectroscopic analysis, including (1) H-, (13) C-NMR, 2D-NMR (HMBC, HSQC, ROESY), and HR-ESI-MS. Evaluation of all isolates for their inhibitory effects on nitric oxide (NO) production was conducted on lipopolysaccaride-activated RAW264.7 macrophages. Compounds 2, 3, 5, and 6 showed inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The analysis of the 1 H-NMR data in conjunction with the HSQC spectrum revealed the presence of two oxygenated methines, an oxygenated methylene, three olefinic protons, six alphatic methylenes, three alphatic methines and three singlet methyls (Table 1, Figures S1–S6). The whole characteristic data of 1 H- and 13 C-NMR indicated that 1 was a 13, 14-seco-withanolide analogue of minisecolide C [17]. The olefinic proton signals at δ H 5.65 (1H, dt, J = 9.4, 4.0 Hz), 6.08 (1H, d, J = 9.4 Hz) and 5.69 (1H, dd, J = 5.2, 2.2 Hz) in the 1 H-NMR, combined with the HMBC correlations from H-4 to C-2, C-3, C-6 and C-10 as well as from H-6 to C-5 and C-10, indicated that conjugated double bonds existed between C-3 and C-6.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of the 1 H-NMR data in conjunction with the HSQC spectrum revealed the presence of two oxygenated methines, an oxygenated methylene, three olefinic protons, six alphatic methylenes, three alphatic methines and three singlet methyls (Table 1, Figures S1–S6). The whole characteristic data of 1 H- and 13 C-NMR indicated that 1 was a 13, 14-seco-withanolide analogue of minisecolide C [17]. The olefinic proton signals at δ H 5.65 (1H, dt, J = 9.4, 4.0 Hz), 6.08 (1H, d, J = 9.4 Hz) and 5.69 (1H, dd, J = 5.2, 2.2 Hz) in the 1 H-NMR, combined with the HMBC correlations from H-4 to C-2, C-3, C-6 and C-10 as well as from H-6 to C-5 and C-10, indicated that conjugated double bonds existed between C-3 and C-6.…”
Section: Resultsmentioning
confidence: 99%
“…The genus Eriolarynx Miers is found in Peru, Bolivia, and the hot and humid forest of Sierra de Aconquija in northwestern Argentina between the elevation of 1000 and 2000 m. Withanolides isolated from this species have been studied for various biological activities, including anti-inflammatory activity, the induction of quinone reductase, and cytotoxic activity [ 18 , 102 , 103 ]. Sebastián J. Castro et al found four new withanolides, 100 – 103 ( Figure 12 ), from Eriolarynx and Deprea, which were evaluated for their anti-cancer activities against A549, HBL-100, HeLa, SW1573, T-47D, and colon adenocarcinoma (WiDr) solid tumor cell lines [ 104 ].…”
Section: Withanolides As Anti-cancer Agentsmentioning
confidence: 99%
“…Several unique withanolides, such as physalins and withaphysalins, were isolated from this plant [ 133 ]. Ru Lin et al isolated four new withanolides, 152 – 155 ( Figure 21 ), and their structures were confirmed using extensive spectroscopic techniques [ 102 ]. These compounds were evaluated for their NO inhibitory effects on LPS-activated RAW 264.7 macrophages to explore their potential anti-inflammatory activity.…”
Section: Withanolides As Anti-inflammatory Agentsmentioning
confidence: 99%
“…franchetii are the most commonly studied for the separation of biologically active compounds and have been used for the therapy of cough, pharyngitis, sore throat, excessive phlegm, dysuria, pemphigus, etc., in traditional Chinese medicine . P. minima, known as ‘Xiao‐Suan‐Jiang’ in China, has a long history of applications as a folk medicine and has been used for treating a variety of human diseases, such as cancer, soreness, pyretic symptoms and inflammation . Moreover, the reported pharmacological activity of withanolides are associated with the application of traditional folk medicines of the genus.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%